Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Pendapatan Bank Syariah - Zaenudin, Zaenudin; Erlina, Yoshi (Al-Iqtishad: Journal of Islamic Economics, 2013)
Financing is one of the key factors of the development of the Islamic banking industry. Islamic bank financing should be ideally dominated by the profit-loss agreement, in which the system is run with the profit sharing system. In using regression analysis, correlation, and hypothesis testing. This study aimed to analyze the impact of mudharabah and musyarakah financing toward revenue in Bank Muamalat Indonesia. The research result showed that the financing of the profit sharing system either partially or simultaneously have a strong and significant influence on Islamic banking income.DOI: 10.15408/aiq.v5i1.2109